History taking in clinical practice - Mahbubani, Krsna (Cham : Springer, 2023)
This book provides a simplified guide to history taking by assessing each symptom in detail, highlighting what key questions are important to ask, and which key differentials are essential to rule out. The chapters are well presented and organised in a logical manner, utilising an easily accessible and user-friendly format for solid learning on focused history taking that includes both general and specific information gathering. History Taking in Clinical Practice includes case-based examples throughout as well as short exercises to enhance learning. GPs, junior doctors and medical students seeking an effective approach to history taking will find this book to be an essential resource for daily clinical practice and exam preparation.
Abnormal Bleeding during Pregnancy (Table 8.1) -- Abnormal Pain during Pregnancy -- Itching in Pregnancy -- Dermatological Causes -- Systemic Causes -- Vomiting in Pregnancy -- Practice Cases -- Chapter 9: Paediatric Histories -- The Febrile Child -- Respiratory tract -- Common Viral Respiratory Tract Infections in Children -- Bacterial Respiratory Tract Infections in Children (Table 9.2) -- Urinary Tract Infections -- Gastrointestinal -- Other Viral Infections (Table 9.3) -- Rarer Causes of Fever in a Child (Table 9.4) -- Enuresis-Bed Wetting -- Abdominal Pain -- Acute Abdominal Pain
Chronic Abdominal Pain
Description based on online resource; title from digital title page (viewed on September 06, 2023).
Added to collection customer.56279.3
Keywords: Medical history taking; Medical History Taking; Anamnèse.; Medical history taking